Aprovechamiento de lodos procedentes del procesamiento de harina de pescado de Tadel S.A. como alternativa en recuperar suelos para uso forestal - Marquinez Moncayo, Julio Abigail (2021)
The investigation consisted in the use of sludge from the processing of fishmeal TADEL S.A. as an alternative in the recovery of soils for forest use. Observation and field techniques were applied to characterize the residual sludge, where physical parameters (humidity, pH, EC), chemical (N, P, Cd, Pb) and microbiological (fecal coliforms) were measured, which helped to determine the sludge as Class C, exclusively for forestry use. Likewise, the physical parameters (pH, EC) and chemical (N, P, Cd, Pb) of the soil were measured to know its degradation. The mud was mixed with degraded soil and it was validated by a single factor DCA experimental design with 4 treatments and 3 replications T1 (0% LR + 100% SD), T2 (10% LR + 90% SD), T3 (20% LR + 80% SD) and T4 (30% LR + 70% SD). Once the combinations were established with the mixture, 25 seeds of the forest species Gmelina arborea Roxb were sown in each experimental unit which, after 30 days, it was found that T3 resulted with greater efficiency in the germination percentage. In addition, the analysis cost ($ 37.10) of said treatment revealed that the use of sludge is an economical way to recover degraded soils, and at the same time it is considered the best way to give proper management and final disposal by the company.